Synthesis, characterization and antimycobacterial activity of Ag(I)-aspartame, Ag(I)-saccharin and Ag(I)-cyclamate complexes - Cavicchioli, Mauricio; Leite, Clarice Q. F.; Sato, Daisy N.; Massabni, Antonio Carlos [UNESP] (Wiley-Blackwell, 2007)
The present work describes the synthesis and antimycobacterial activity of three Ag(I)-complexes with the sweeteners aspartame, saccharin, and cyclamate as ligands, with the aim of finding new candidate substances for fighting tuberculosis and other mycobacterial infections. The minimal inhibitory concentration of these three complexes was investigated in order to determine their in-vitro antimycobacterial activity against Mycobacterium tuberculosis, Mycobacterium avium, Mycobacterium intracellulare, Mycobacterium malmoense, and Mycobacterium kansasii. The MIC values were determined using the Microplate Alamar Blue Assay. The best MIC values found for the complexes were 9.75 mu M for Ag(l)-aspartame against M. kansasii and 15.7 mu M for Ag(I)-cyclamate against M. tuberculosis.
Keywords: antimycobacterial activity; MABA; silver-aspartame; silver-cyclamate; silver-saccharin